2009
DOI: 10.1021/jp906603r
|View full text |Cite
|
Sign up to set email alerts
|

Are Spin-Forbidden Crossings a Bottleneck in Methanol Oxidation?

Abstract: The rate of spin-surface crossing from the singlet to the triplet potential energy surface during methanol oxidation has been examined for classically spin-forbidden crossings. The Landau−Zener equation has been used to calculate the thermally-averaged spin transition probabilities for the nonadiabatic surface crossing reaction. Two active sites have been investigated: isolated vanadate species supported on silica (VO x /SiO2) and titania (VO x /TiO2). The results show that the rate of spin-surface crossing is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 20 publications
3
36
0
1
Order By: Relevance
“…In this case, the higher-order contributions to spinorbit coupling, spin-orbit vibronic coupling, and spin-spin coupling in Eq. (16), which are usually assumed to be small, could become responsible for the interaction between the diabatic states and ultimately for the non-zero intersystem crossing rates.…”
Section: Tutorial Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the higher-order contributions to spinorbit coupling, spin-orbit vibronic coupling, and spin-spin coupling in Eq. (16), which are usually assumed to be small, could become responsible for the interaction between the diabatic states and ultimately for the non-zero intersystem crossing rates.…”
Section: Tutorial Reviewsmentioning
confidence: 99%
“…[6][7][8] The magnetic properties of transition metal complexes and materials can be controlled by light, temperature, and pressure by initiating spin-crossover transitions between the low-spin and high-spin states. [9][10][11][12] Among many examples of processes where intersystem crossings play a central role are combustion, [13,14] reactions in the atmosphere and in interstellar space, [5,15] transition metal-based catalysis, [16] and binding of small molecules to the active sites of metalloproteins. [17][18][19][20] Intersystem crossing has applications in photodynamic therapy, [21,22] free-radical polymerization reactions, [23] organic-light emitting diodes, [24][25][26] and metal-organic frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…Spin-orbit coupling and probability of crossing would be necessary to determine if the spin-crossing is rate limiting. [63][64][65] Recently, Goodrow et al 63 have calculated the thermally averaged spin transition probabilities for the nonadiabatic surface crossing in isolated vanadate species supported on silica and titania for the selective methanol oxidation to formaldehyde. The authors concluded that the rate of spin-surface crossing is much faster than the rate-limiting H-abstraction step and is, therefore, not kinetically relevant.…”
Section: Implications Of the Spin-crossing Point In The Kinetics Of Tmentioning
confidence: 99%
“…The weighted average with statistical concepts based on the Landau‐Zener (LZ) model was introduced to evaluate the ISC probabilities at the MECP, which is defined as Equation . The LZ probability for the mass‐weighted component of the nuclear velocity perpendicular to the crossing seam and the Maxwell‐Boltzman velocity distribution, as is shown in Equations and . For kinetics of nonadiabatic spin‐forbidden reaction, we roughly estimated the rate constant based on the transition state theory Equation .…”
Section: Computation Methodsmentioning
confidence: 99%
“…The LZ probability for the mass-weighted component of the nuclear velocity perpendicular to the crossing seam and the Maxwell-Boltzman velocity distribution, as is shown in Equations (3) and (4). [59,60] For kinetics of nonadiabatic spin-forbidden reaction, we roughly estimated the rate constant based on the transition state theory Equation (6). [61] It should be noted that the equation of P ISC = 1 − P LZ , P LZ is the LZ probability from one adiabatic state to another adiabatic state, while P ISC is hopping probability from one non-adiabatic state to another state PES via nonadiabatic transition.…”
Section: Soc Calculationsmentioning
confidence: 99%